Working capital management and corporate profitability: Empirical evidence from Vietnam - Nguyễn, Thanh Hồng Ân (Sciendo-De Gruyter, 2022)
This paper examines the relationship between working capital management and corporate profitability of Vietnamese listed firms. We propose a different interpretation of the empirical evidence that takes into account the dependency of collection and payment decisions. This helps establish the causal relationship between working capital management and firm profitability, which made the interpretation of the empirical results more meaningful and consistent with the real practice of firms. The analysis results based on a sample of 374 Vietnamese listed firms in the period from 2008 to 2014 show that working capital management positively affects the performance of Vietnamese listed companies. However, the results also indicate that Vietnamese firms do not intentionally use trade credit policy to enhance firms’ performance and the observed relationship between trade credit and profitability, though significant, is just by coincidence.